Avian malaria in birds from Atlantic Rainforest: a record of Plasmodium cathemerium and other novel lineages - TALYS H.A. JARDIM; MARIANA F. ROSSI; HUARRISSON A. SANTOS; MARTA T. D'AGOSTO; ROBERTO JÚNIO P. DIAS (Anais da Academia Brasileira de Ciências)
Abstract Parasitic diseases, like avian malaria, play a relevant impact on wild avifauna around the world, putting a threat to biodiversity, principally in endemic zones. For this research, we collected 171 blood samples from 21 wild bird species in different locations within Atlantic Rainforest, a global avian endemism center. These samples were analyzed using a morphological, molecular, and phylogenetic approach. Our findings reveal the presence of Plasmodium cathemerium, a widespread and pathogenic parasite species in bird hosts. Furthermore, we recovered another 4 new genetic lineages of avian malaria parasites, enriching knowledge about these haemosporidians in the Atlantic Rainforest and Brazil.